Test design for measuring the kinematic velocity of the lower extremities of volleyball - Khalaf, Naima Zaidan; Ali, Intisar Owaid; faiq, wafaai (International Journal of Psychosocial Rehabilitation, 2020)
Volleyball game is one of the group games with different changing positions with a fast and changing rhythm, which requires players physical and motor capabilities commensurate with the changes witnessed in the matches, especially the decisive and converging results, so kinetic speed is an important motor characteristic of the volleyball player, especially during play as a result The player needs to perform repeated and rapid movements and frequencies to reach the location of the ball before it falls to the ground, which requires the player to have a correct rapid movement speed at the appropriate time appropriate to the playing situations. Therefore, the importance of the research lies in adopting the correct scientific method to design a specialized test that measures the kinematic speed of the lower sides of the volleyball to measure the kinetic speed of volleyball players to advance the level of volleyball and to create a good and accurate vision of the kinetic state of the player in order to provide appropriate solutions that serve the coach to modify the progress path according to What is needed in the team’s training process. So the aim of the research was to: Design a test to measure the kinematic velocity of the lower extremities in volleyball, and the descriptive approach was used on students of the fourth stage of the Faculty of Physical Education and Sports Science for girls, who are (91) students, and the raw grades were converted to modified standard degrees, and the researchers concluded that the designed test proved valid To measure the kinetic velocity of the lower extremities of volleyball, researchers recommend using a test designed to measure the kinetic velocity of the lower volleyball.